Diagnostic and therapeutic biomarker responses in HIV and tuberculosis co-infected patients - Mthiyane, Thuli Carol Penelope (Department of Medicine, 2021)
Introduction: Biomarkers of tuberculosis (TB) diagnosis and treatment response in patients coinfected with human immunodeficiency virus (HIV) are a necessity to ensure early diagnosis and adequate monitoring of TB treatment response. We conducted 3 sub-studies: study 1 was a bioavailability study; study 2 was a PK study in HIV-TB co-infected persons, and study 3 evaluated a WHO-recommended treatment algorithm in TB-HIV co-infected persons. Study 1 and 2 contributed to the study of 2 (NAT2) polymorphisms. Study 1 was leveraged to evaluate Quantiferon Gold in tube (QFT-GIT) and a quality of life instrument as a longitudinal biomarker in smear and culture positive TB-HIV co-infected patients. Study 3 was leveraged to study urine lipoarabinomannan (LAM) as a diagnostic adjunct in smear-negative HIV-infected patients treated for TB. Methods: Blood was collected from participants with HIV-infection only and TB-HIV coinfection for NAT2 polymorphisms at baseline, and for QFT-GIT at baseline, month 3, 6 and 12; a health-related quality-of-life (HRQOL) instrument was applied at the same timepoints to monitor treatment response in Study 1. An additional 40 TB-HIV co-infected participants (Study 2) were included in the analysis for the assessment of NAT2 polymorphisms and its effect on isoniazid plasma levels and hepatotoxicity. Urine was collected from seriously ill HIV-infected patients with confirmed smear-negative presumptive-TB (Study 3) prior to anti-TB treatment and tested using a commercially available LAM-ELISA. Blood and sputum were collected and processed for TB culture. Results: One hundred and twenty participants (100 TB-HIV co-infected and 20 non-TB but HIVinfected) from Study 1 and Study 2 with genotype results and were evaluated. Percentage of metabolisers in each category were: slow 52.5% (63/120), (NAT2*5/*5); intermediate 35.8% (43/120), (NAT2*4/*5 and NAT2*5/12); and rapid 11.7% (14/120), (NAT2*4/*11, NAT2*11/12 and NAT2*12/12). In general, isoniazid area under the concentration curve (AUC)0-∞ and maximum concentration (Cmax) were lower amongst the study 1 compared to study 2 participants. INH and AcINH PK parameters across genotypes were not statistically significantly different within each study. The log AcINH: log INH ratio, calculated as a measure of acetylation at two and four hours post-dose, showed no statistically significant difference between genotypes.